Efek Ekstrak Etanol Kulit Petai (Parkia speciosa) Terhadap Fungsi Hepar Rattus norvegicus yang Terpapar Minyak Goreng Bekas - Fafa Nurdyansyah; Dyah Ayu Widyastuti; Andita Ayu Mandasari (Fakultas Farmasi Universitas Pancasila, 2021)
The use of cooking oil repeatedly is one of liver damage trigger which usually be marked byenhancement of SGPT and SGOT level. The objective of this study is to know the eff ect of P. speciosa peelethanolic extract in used cooking oil exposed Wistar rats (R. norvegicus). The indicator are SGPT and SGOTconcentration. Parkia speciosa peel was extracted then use to antioxidant source. Rattus norvegicus was divided into 4 group. Group 1 with no treatment, group 2 with 1 ml used cooking oil 118 mek/kg and 100 mg/l extract, group 3 with 1 ml used cooking oil 118 mek/kg and 200 mg/l extract, and group 4 as positive control with 1 ml used cooking oil 118 mek/kg. Each group serum sample was analyzed for SGPT and SGOT. The result showed that 200 mg extract treatment is signifi cantly bring lower SGPT and SGOT concentration compared to positive control. The higher dose of ethanolic extract of P. speciosa peel is highly prevent liver damage which indicated by the lower SGPT and SGOT concentration in serum. The ethanolic extract of P. speciosa peel has potential to ward off free radicals which caused by used cooking oil exposed. That fact was be marked by SGPT and SGOT decreasing persentage.